DESIGN OF WEB-BASED FIXED ASSETS FOR LOAN SYSTEM AT CLASS II A COMMUNITY INSTITUTIONS BANCEUY BANDUNG - Guntur Salasa Priambodo; Candra Mecca Sufyana (STMIK Dian Cipta Cendikia Kotabumi, 2021)
This research was conducted at the Class II-A Banceuy Penitentiary. The problem in this research is the system of borrowing goods in the form of fixed assets which is still done traditionally. This research has a goal, namely to design a system for borrowing goods in the form of web-based fixed assets at the Class II-A Banceuy Penitentiary in Bandung. The waterfall method is used in this research. The data collection process was carried out using interviews and field observations. The next process is designing the database and UI, and then doing the coding process using the PHP and MySQL programming languages to create a database. The information system for borrowing goods in the form of fixed assets was created with features to view inventory data, input goods in, input goods out. The need for this functional system has been tested, and the process is in accordance with the existing business activities at the Class II-A Banceuy Penitentiary Bandung. The system helps so that the process of borrowing goods can be carried out easily by Banceuy prison staff and can also view inventory data, so that the performance and service felt by the staff are optimal. Keywords: Web-Based Goods Lending System, Fixed Assets, Class II-A Correctional Institution Banceuy Bandung